SPE International Symposium on Oilfield Chemistry 2013
DOI: 10.2118/164130-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Finding in the Interaction Between Chelating Agents and Carbonate Rocks During Matrix Acidizing Treatments

Abstract: During matrix acidizing, successful iron control can be critical to the success of the treatment. Iron (III) precipitation occurs when acids are spent and the pH rises above 1, which can cause severe formation damage. Chelating agents are used during these treatments to minimize iron precipitation.In this paper, we studied the effect of iron precipitation in acidizing operations. HCl solutions (5 -20 wt%) containing 5,000 to 10,000 ppm of Fe 3+ were used in these experiments. Biodegradable GLDA (glutamic-N, N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The results showed that NTA decomposed completely at 300°F and partially (23%) at 250°F and the authors highlighted the need to investigate alternatives of iron chelating agents at these conditions. Assem et al (2013aAssem et al ( , 2013b examined glutamic N,N-diacetic acid or (GLDA) as an iron chelating agents used with HCl. Acid solutions (5 -20 wt%) with a loading of 5,000 and 10,000 ppm of Fe 3ϩ were tested at 200°F.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that NTA decomposed completely at 300°F and partially (23%) at 250°F and the authors highlighted the need to investigate alternatives of iron chelating agents at these conditions. Assem et al (2013aAssem et al ( , 2013b examined glutamic N,N-diacetic acid or (GLDA) as an iron chelating agents used with HCl. Acid solutions (5 -20 wt%) with a loading of 5,000 and 10,000 ppm of Fe 3ϩ were tested at 200°F.…”
Section: Introductionmentioning
confidence: 99%